Never slow dance with a zombie - Van Lowe, Ehrich (New York : Tor, 2009)
When most of their high school classmates turn into flesh- eating zombies, Margot and best friend Sybil see an opportunity to finally become popular and find boyfriends- -if they can just stay alive.
"A Tom Doherty Associates book."
Keywords: Best friends -- Fiction; Friendship -- Fiction; Zombies -- Fiction; Popularity -- Fiction; High schools -- Fiction; Schools -- Fiction